When grassroots innovation movements encounter mainstream institutions: implications for models of inclusive innovation - Fressoli, Juan Mariano (2014)
Grassroots innovation movements (GIMs) can be regarded as initiators or advocates of alternative pathways of innovation. Sometimes these movements engage with more established science, technology and innovation (STI) institutions and development agencies in pursuit of their goals. In this paper, we argue that an important aspect to encounters between GIMs and mainstream STI institutions is the negotiation of different framings of grassroots innovation and development of policy models for inclusive innovation. These encounters can result in two different modes of engagement by GIMs; what we call insertion and mobilization. We illustrate and discuss these interrelated notions of framings and modes of engagement by drawing on three case studies of GIMs: the Social Technologies Network in Brazil, and the Honey Bee Network and People's Science Movements in India. The cases highlight that inclusion in the context of GIMs is not an unproblematic, smooth endeavour, and involves diverse interpretations and framings, which shape what and who gets included or excluded. Within the context of increasing policy interest, the analysis of encounters between GIMs and STI institutions can offer important lessons for the design of models of inclusive innovation and development.